A systematic review with meta-analysis: Traditional Chinese tuina therapy for insomnia - Wang, Zheng; Xu, Hui; Zhou, Hang; Lei, Yang; Yang, Lulu; Guo, Juan; Wang, Yuxia; Zhou, Yunfeng (Frontiers in Neuroscience, 2023)
Background: With changes in the way of life and work, an increasing number of people are suffering from insomnia. In China, a traditional Chinese medicine method tuina is widely used for the treatment of insomnia. However, the evidence for tuina therapy for insomnia remains controversial. Therefore, this systematic review aimed to evaluate the effect of tuina massage therapy on the symptoms of patients with primary insomnia. Methods: From establishment to January 2022, a comprehensive literature search was conducted using seven electronic databases to identify randomized controlled trials of tuina therapy for insomnia. We applied RevMan 5.4 and GRADE Pro-GDT to evaluate the quality of the included RCTs and perform the meta-analysis. The methodological quality of the included studies was assessed using the Cochrane risk-of-bias tool. Subgroup analysis was performed according to the different intervention methods. The I2 statistic was used to assess the heterogeneity. Results: Eighteen studies conducted from 2011 to 2021 were included, with a total of 1471 patients. In terms of efficacy, tuina alone was superior to other treatments (OR, 3.46; 95% CI, 2.15,5.55; P<0.00001); tuina combined with other treatments (acupuncture, scraping, auricular acupuncture, Suanzaoren decoction, estazolam) was more effective than other single therapies (OR, 3.99; 95% CI, 2.84,5.61; P<0.00001). In terms of Pittsburgh Sleep Quality Scale (PSOI)score, the improvement in insomnia patients by tuina alone was better than that of other treatments (MD, -2.57; 95% CI, -2.98,-2.17; P<0.00001), and tuina combined with other treatments (acupuncture, scraping, auricular point pressing, Suanzaoren decoction, estazolam) was better than other single therapies (MD, -2.83; 95% CI, -2.98,-2.68; P<0.00001). Conclusion: There is positive evidence that tuina is a beneficial therapy for primary insomnia. However, owing to the small sample size, evidence supporting the long-term efficacy of tuina in patients with insomnia is limited.